2012
DOI: 10.2967/jnumed.111.098350
|View full text |Cite
|
Sign up to set email alerts
|

Variable Lung Density Consideration in Attenuation Correction of Whole-Body PET/MRI

Abstract: Present attenuation-correction algorithms in whole-body PET/ MRI do not consider variations in lung density, either within or between patients; this may adversely affect accurate quantification. In this work, a technique to incorporate patient-specific lung density information into MRI-based attenuation maps is developed and compared with an approach that assumes uniform lung density. Methods: Five beagles were scanned with 18 F-FDG PET/CT and MRI. The relationship between MRI and CT signal in the lungs was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…Before each PET scan, MR images were acquired to correct for photon attenuation. Attenuation correction was performed using 2-point Dixon MR images as previously described (16,17). Data acquisition spanned over 10 min and began a few seconds before the 13 N-ammonia injection.…”
Section: Animal Model and Preparationmentioning
confidence: 99%
“…Before each PET scan, MR images were acquired to correct for photon attenuation. Attenuation correction was performed using 2-point Dixon MR images as previously described (16,17). Data acquisition spanned over 10 min and began a few seconds before the 13 N-ammonia injection.…”
Section: Animal Model and Preparationmentioning
confidence: 99%
“…Hofmann and colleagues 33 studied an MR-guided attenuation correction technique using image segmentation and a method based on an atlas registration and pattern recognition (AT&PR) algorithm in 11 patients and reported that the MR-guided technique using AT&PR provided better overall PET quantification accuracy than the basic MR image segmentation approach because of the significantly reduced volume of errors made regarding volumes of interest within or near bones and the slightly reduced volume of errors made regarding areas outside the lungs. Marshall and colleagues 34 developed a technique wherein variable lung density was taken into account in the attenuation correction of whole-body PET-MR imaging. The investigators first established a relationship between MR imaging and CT signal in the lungs and used it to predict attenuation coefficients from MR imaging.…”
Section: Mr Imaging-guided Attenuation Correction In Pet-mrmentioning
confidence: 99%
“…Therefore, multiple groups have developed segmentation-based methods for whole-body MR-based AC that do not account for the bone without compromising the quantification accuracy for regions that are not close to osseous tissue. Lung segmentation needs to be addressed because the lung density between patients is highly variable, which can affect the quantification results (47). However, the lung signal intensity is generally low in images acquired with conventional MR sequences.…”
Section: Acmentioning
confidence: 99%